When your mind wants something and……your body does another” Art therapy and cerebral palsy - Ana Viñuelas Lorenzo (Arteterapia)
We daily pass by without noticing the movements our body achieves smoothly and fluently. We move, we act, and we interact physically with the environment and we are rarely aware of that. What happens when your head orders something and your body does something totally different? What happens when due to disturbances of communication and behaviour, relationship with the rest of the world is not standard and no one understands? It is not that frequent to find situations where your body as a whole determines so much life, perception, behaviour, communication… such as in the case of people suffering cerebral palsy. Art- therapy has much to offer in this area due to the fact that time, codes regarding relations and expected outcomes are not defined. The participants involved will create a new language, a new way for communication with neither boundaries nor constraints. Body is no longer a hindrance but a feature to be taken into account.